PENGARUH TEKANAN EKSTERNAL, KETIDAKPASTIAN LINGKUNGAN, KOMITMEN ORGANISASI DAN TINGKAT PENGUNGKAPAN LAPORAN KEUANGANTERHADAP PENERAPAN TRANSPARANSI PELAPORAN KEUANGAN (Studi Empiris Pada SKPD Kabupaten Kampar) - Abang Reza Yunaz; Raja Adri Satriawan Surya; Alfiati Silfi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2016)
The research purpose is to analyzing the effect of external pressure, environment uncertainty, organization commitment and the range of explanation finance report toward implementation of the transparency of financial report in SKPD Kampar district. The analytical method that used is multiple regression t-test to see the impact of each independent variable toward dependent variable. This research uses primary data by distributing questionnaires to 93 sample from echelon 2 and 3 at SKPD Kampar district government. Based on analysis result, it is known that the independent variable that have effect toward implementation of the transparency of financial report is external pressure, environment uncertainty, and the range of explanation finance report. As for the other variable is organization commitment proven has no effect on implementation of the transparency of financial report. The coefficient determination of this research is 13.7%, while 86.3% explained by other variables that not included in this research model.Keywords : transparency, finance, pressure, uncertainty and commitment